"Essential" services, risk, and child protection in the time of COVID-19: An opportunity to prioritize chronic need. (September 2020) - Caldwell, Johanna; Delaye, Ashleigh; Esposito, Tonino; Petti, Tara; Black, Tara; Fallon, Barbara; Trocmé, Nico
In many North American jurisdictions, socioeconomically vulnerable families are more likely to be involved with child protection systems and experience ongoing challenges. The current public health response to the COVID-19 pandemic is having a disproportionate impact on these families via unemployment, "essential" work, isolation, and closures of childcare and schools, with negative implications for children's developmental wellbeing. Experts warn that while child protection referrals have gone down, children who are at risk of maltreatment are less exposed to typical reporters (e.g., school professionals). At the same time, physical distancing measures are prompting many human service settings to shift toward virtual intervention with children and families. In this commentary, we suggest that a focus on short-term risk in the response to COVID-19 may obscure support for children's long-term outcomes. We propose two policy considerations: (1) in the immediate term, that child protection workers be deemed "essential"; and (2) in the longer term, that permanent, universal basic income guarantees be implemented to support a baseline of predictability both in families' material wellbeing and in fiscal budgets in the case of a future crisis. As we write, it is impossible to predict the longevity of these closures nor the extent of their impact on children and families. However, the present article mirrors commentary following previous crises noting the importance of going beyond immediate health risk mitigation to consider wellbeing with regard to children's development and families' socioeconomic needs in the long term.